2022
DOI: 10.33448/rsd-v11i10.32702
|View full text |Cite
|
Sign up to set email alerts
|

Condição periodontal associada à prática de higiene bucal e ao hábito de fumar de pacientes do serviço de periodontia da Universidade Estadual da Paraíba

Abstract: O objetivo deste trabalho é avaliar a condição periodontal de pacientes atendidos na clínica escola de Odontologia da Universidade Estadual da Paraíba – UEPB, campus I, Campina Grande, Paraíba, investigando sua associação com as características comportamentais e hábitos da população estudada. Trata-se de um estudo transversal, quantitativo e analítico a partir de prontuários odontológicos. Utilizou-se como critérios de exclusão a incompletude de dados ou a falta de assinatura do TCLE pelo paciente. As análises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Extensive literature demonstrates that smokers have worse oral health, represented by a greater number of periodontal problems, a greater number of missing dental elements, higher prevalence of oral cancer, among other diseases (Pereira et al, 2014;Dietrich et al, 2007;Ahsan et al, 2020;Alves et al, 2017;Lopes et al, 2021;Santos et al, 2022), which partially corroborates the findings of this study, since it identified, for example, a worse periodontal condition among smokers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Extensive literature demonstrates that smokers have worse oral health, represented by a greater number of periodontal problems, a greater number of missing dental elements, higher prevalence of oral cancer, among other diseases (Pereira et al, 2014;Dietrich et al, 2007;Ahsan et al, 2020;Alves et al, 2017;Lopes et al, 2021;Santos et al, 2022), which partially corroborates the findings of this study, since it identified, for example, a worse periodontal condition among smokers.…”
Section: Discussionsupporting
confidence: 87%
“…Tobacco is also associated with the occurrence of deleterious effects on oral health. Several previous studies demonstrate that smokers have a higher risk of tooth loss (Pereira et al, 2014;Dietrich et al, 2007), higher prevalence of periodontal diseases, dental caries and leukoplasia (Ahsan et al, 2020;Santos et al, 2022) as well as a higher risk of developing oral squamous cell carcinoma (Alves et al, 2017;Lopes et al, 2021). On the other hand, the literature is scarce on a possible impact of smoking on oral health-related quality of life (OHRQoL) (Bakri et al, 2018;Sagtani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%